Efficacy of malic and tartaric acid in mitigation of cadmium stress in Spinacia oleracea L. via modulations in physiological and biochemical attributes - Ansa Shabbir; Anis Ali Shah; Sheeraz Usman; Shakil Ahmed; Muhammad Kaleem; Shiffa Shafique; Mansour K. Gatasheh (Scientific Reports)
Abstract The increasing level of cadmium (Cd) contamination in soil due to anthropogenic actions is a significant problem. This problem not only harms the natural environment, but it also causes major harm to human health via the food chain. The use of chelating agent is a useful strategy to avoid heavy metal uptake and accumulation in plants. In this study, randomized design pot experiment was conducted to evaluate potential role of malic acid (MA) and tartaric acid (TA) foliar spray to mitigate Cd stress in Spinacia oleracea L plants. For Cd stress, S. oleracea plants were treated with CdCl2 solution (100 µM). For control, plants were given distilled water. One week after Cd stress, MA and TA foliar spray was employed at concentration of 100 and 150 µM for both. The results of this study revealed that Cd stress (100 µM) significantly reduced growth attributes, photosynthetic pigments and related parameters and gas exchange attributes. Cadmium stress also stimulated antioxidant defense mechanism in S. oleracea. Cd stressed plants had elevated levels of Cd metal ions in root and consumable parts (i.e. leaves) and caused severe oxidative damages in the form of increased lipid peroxidation and electrolytic leakage. MA and TA supplements at both low and high levels (100 and 150 µM) effectively reversed the devastating effects of Cd stress and improved growth, photosynthesis and defense related attributes of S. oleracea plants. These supplements also prevented excessive accumulation of Cd metal ions as indicated by lowered Cd metal contents in MA and TA treated plants. These findings demonstrated that MA and TA treatments can potentially reduce Cdl induced phytotoxicity in plants by reducing its uptake and enhancing photosynthesis and defense related parameters.